House passes bill to increase visas for high-tech workers, adds safeguards for Americans. - Gravely, Bob (CQ Weekly, 1998)
On September 24, 1998, the House passed a compromise bill (HR 3736) to increase the number of visas that give permission to highly skilled workers such as computer programmers to gain entry to the U.S. to work. The bill was the product of negotiations between the White House and Spencer Abraham, R-Mich., the legislation's primary sponsor in the Senate. The measure would raise the number of temporary “H-1B” visas available annually from 65,000 to 115,000 in 1999 and 2000 and to 107,500 in 2001—the limit would then return to 65,000. The agreement came after the Clinton administration warned that it would veto the Senate version of the bill (S 1723), which was passed in May, because the administration objected to the absence of protections for American workers.